2017
DOI: 10.1007/s40291-017-0285-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of MicroRNA Heterogeneity in Cancer Biology

Abstract: MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression, involved in the silencing of messenger RNA (mRNA) translation. The importance of miRNA signatures in disease screening, prognosis, and progression of different tumor types and subtypes is increasing. miRNA expression levels change depending on numerous factors. In this review, we are describing the circumstances under which miRNA levels can change, these are named 'levels' of heterogeneity of miRNAs. miRNAs can have oncogenic, tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 90 publications
2
29
0
Order By: Relevance
“…Numerous studies have described so-called "miRNA signatures" associated with specific biological functions, including cancer development and progression [13,85,[98][99][100][110][111][112]. Since one miRNA can regulate up to hundreds of different target genes in a cell [69,113,114], the administration of single miRNAs as therapeutic targets raises the problem of a potentially widespread functional heterogeneity of one miRNA in different tumors types and potential adverse side effects to normal tissue [115,116]. Therefore, research addressing miRNAs as therapeutic targets should focus on miRNAs that majorly or desirably act solely as tumor-suppressors or oncogenes in one specific setting to avoid mutual neutralization effects.…”
Section: Specific Mirnas As Therapeutic Agents In Melanoma and Hcc-a mentioning
confidence: 99%
“…Numerous studies have described so-called "miRNA signatures" associated with specific biological functions, including cancer development and progression [13,85,[98][99][100][110][111][112]. Since one miRNA can regulate up to hundreds of different target genes in a cell [69,113,114], the administration of single miRNAs as therapeutic targets raises the problem of a potentially widespread functional heterogeneity of one miRNA in different tumors types and potential adverse side effects to normal tissue [115,116]. Therefore, research addressing miRNAs as therapeutic targets should focus on miRNAs that majorly or desirably act solely as tumor-suppressors or oncogenes in one specific setting to avoid mutual neutralization effects.…”
Section: Specific Mirnas As Therapeutic Agents In Melanoma and Hcc-a mentioning
confidence: 99%
“…While approximately 300 miRNAs have demonstrated a role in carcinogenesis, more than 2000 miRNAs have been found differentially expressed in human cancers (Yang et al, 2017) and evidence that different types of cancer can be discriminated by miRNA profiling has been reported (Iorio & Croce, 2017;Petrovic, Ergün, & Isenovic, 2017). In cutaneous melanoma, there is increasing evidence for a significant role of specific miRNAs as oncogenes or tumour suppressor genes (Mione & Bosserhoff, 2015;Mirzaei et al, 2016;Varamo, Occelli, Vivenza, Merlano, & Lo Nigro, 2017) as well as their involvement in other aspects of melanoma biology (Leibowitz-Amit, Sidi, & Avni, 2012;Luo, Weber, Osen, Bosserhoff, & Eichmuller, 2014;Sun, Zhou, Majid, Kashani-Sabet, & Dar, 2014;Voller, Ott, & Bosserhoff, 2013).…”
Section: G Ener Al Fe Ature S Of Mirna Smentioning
confidence: 99%
“…Previous studies have shown that miRNA dysregulation is involved in the development of EC and that miRNAs act as both oncogenes and tumor suppressor genes. [16][17][18] He et al divided human EC cell lines KYSE170 and ECA109 into two groups: one cultured in RPMI 1640 medium containing 10% fetal bovine serum (FBS) and the other in RPMI 1640 medium containing 10% FBS plus 50 μM/L ZnSO 4 . The miRNA levels in the two cell lines were then measured to analyze the influence of the Zn level on the miRNAs.…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
“…Micro‐RNAs (miRNAs, miRs) are non‐coding RNAs approximately 18–22 nucleotides in length that post‐transcriptionally regulate gene expression by base‐pairing to partially complementary sequences in the 3′‐untranslated region (UTR) of their target messenger RNA (mRNA). Previous studies have shown that miRNA dysregulation is involved in the development of EC and that miRNAs act as both oncogenes and tumor suppressor genes …”
Section: Introductionmentioning
confidence: 99%